1996
DOI: 10.1103/physrevb.54.7470
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation-induced in-plane conductivity, magnetoconductivity, and diamagnetism ofBi2Sr2

Abstract: We report detailed experimental results on the fluctuation-induced in-plane conductivity ⌬ ab , magnetoconductivity ⌬ ab , and diamagnetism ⌬ ab , of high-quality Bi 2 Sr 2 CaCu 2 O 8 crystals. The data were obtained with magnetic fields H applied perpendicularly to the superconducting ͑CuO 2 ͒ planes and up to 0 Hϭ5 T, which not too close to the transition ͓for reduced temperatures ϵ(TϪT C0 )/T C0 տ10 Ϫ2 ͔ may be considered in the weak magnetic field limit. In the mean field region ͑MFR͒ above the transition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…The fluctuation conductivity obtained for BSCCO in the present work agrees in magnitude with that obtained by Pomar et al [6] in a similar study. However, they have been able to explain their data in terms of the LD model (eq.…”
Section: Results and Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…The fluctuation conductivity obtained for BSCCO in the present work agrees in magnitude with that obtained by Pomar et al [6] in a similar study. However, they have been able to explain their data in terms of the LD model (eq.…”
Section: Results and Analysissupporting
confidence: 93%
“…The DOS or other indirect contributions were not required. Similarly, Pomar et al [6] did not require to invoke these terms in the paraconductivity of Bi 2 Sr 2 CaCu 2 O 8+δ (BSCCO). On the other hand, Livanov et al [7] found significant amounts of σ DOS to be present in their studies on thin films of BSCCO.…”
Section: Introductionmentioning
confidence: 99%
“…A further re® nement of the theory of the in-plane¯uctuation conductivity was carried out considering two di erent interlayer distances and di erent strengths of the tunnelling coupling between adjacent layers for YBCO [142,143] and BSCCO 2212 [144]. This approach led to the same qualitative results as those obtained by the conventional single layer approach, but to a better quantitative agreement between the theory and experiments.…”
Section: In-plane Resistance: Crossover Phenomena Observationsmentioning
confidence: 63%
“…The samples of La-SrCuO are grain aligned with a total mass of 48 mg, thus at least 2 orders of magnitude larger than those crystals used in other fluctuation measurements. [25][26][27][28][29] Such a big mass makes it possible to better detect fluctuations because of the larger temperature range employed. The grains have diameters around 5-10 m, a dimension much bigger than the superconducting coherence length, which determines the thermal fluctuations of Cooper pairs above the transition.…”
mentioning
confidence: 99%